Health risk assessment of cadmium, lead, iron, and zinc exposure from food and cigarettes in Pakistani smokers - Hamza Shafiq; Mamoona Amir; Aneela Hameed; Amir Ismail; Siti Suhaila Binti Harith; Areeba Usman (Journal of Trace Elements and Minerals)
Aim and background: Smoking is a major contributor to illnesses and deaths, strongly associated with cardiovascular disease, lung cancer, and chronic pulmonary diseases. This study aims to analyze the levels of trace metals (Pb, Cd) and their potential impact on vital metals (Fe, Zn) in cigarette smokers and nonsmokers in Multan. Material and methods: This case−control research included 537 human participants with similar socioeconomic status, consisting of four groups based on smoking intensity. Blood, wheat flour, drinking water, and cigarette samples were analyzed for key parameters and concentrations of Cd, Pb, Fe, and Zn. An Analysis of Variance (ANOVA) was performed to assess the differences in metal concentrations across the various sample types. Results: The mean blood concentrations of Cd and Pb were as follows for the control, light, moderate, and heavy smoker groups, respectively; 0.10 and 3.64, 0.12 and 4.40, 0.14 and 4.59, and 0.14 and 5.05 µg dL⁻1. When considering all smoking individuals as a single group, blood Cd and Pb concentrations were 37 % and 28 % higher, respectively, compared to nonsmokers, and almost 53 % of samples exceeded blood-Cd from the safe limits of WHO (0.03−0.12 µg dL⁻1). While concentrations of blood Zn and Fe were almost 10 % lower in all smokers’ groups as compared to nonsmokers, respectively. Furthermore, the results indicated a substantial inverse relationship between the concentrations of Pb and Zn and the blood's Cd and Fe levels. Acceptable values of Cd and Pb were discovered in all wheat flour and water samples. Tobacco from different cigarette brands had exceeding levels of Cd, ranging from 0.03 to 0.21 µg g⁻1 and Pb, 0.49–2.92 µg g⁻1. For cancer risk assessment, the incremental lifetime cancer risk (ILCR) for Cd surpassed about 28.93 % of cigarette samples. Alarmingly, 99 % of cigarette samples exceeded the hazard quotient (HQ) for Cd and Pd, indicating Cd as a huge risk factor. Compared to non-smokers, smokers had higher levels of white blood cells, red blood cells, and hemoglobin with a lower body mass index. Conclusion: These findings underscore cigarette smoking as a major source of Cd and Pb, potentially impacting the levels of Fe and Zn in human blood. Increasing awareness of the risks associated with smoking may prompt a government initiative calling for behavioural interventions.